Vagal impairment of gastric secretion in diabetic autonomic neuropathy. Issue 5971 (14th June 1975) - Hosking, D J; Moody, F; Stewart, I M; Atkinson, M
Abstract : Gastric acid output in response to insulin-induced hypoglycaemia and pentagastrin was measured in 18 diabetic patients with symptoms of autonomic neuropathy. Two patients had achlorhydria but the rest responded normally to pentagastrin. The acid output evoked by insulin-induced hypoglycaemia was low in 10 of the 16 patients who secreted acid in response to pentagastrin. These changes suggest that vagal impairment is common in diabetics with autonomic symptoms, which might explain the infrequency of duodenal ulcer in diabetics.